2018
DOI: 10.1007/s00604-018-2779-5
|View full text |Cite
|
Sign up to set email alerts
|

MnO nanoparticles with unique excitation-dependent fluorescence for multicolor cellular imaging and MR imaging of brain glioma

Abstract: The authors describe MnO nanoparticles (NPs) with unique excitation-dependent fluorescence across the entire visible spectrum. These NPs are shown to be efficient optical nanoprobe for multicolor cellular imaging. Synthesis of the NPs is accomplished by a thermal decomposition method. The MnO NPs exhibit a high r relaxivity of 4.68 mM s and therefore give an enhanced contrast effect in magnetic resonance (MR) studies of brain glioma. The cytotoxicity assay, hemolysis analysis, and hematoxylin and eosin (H&E) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…Size is an important factor, as it affects the tumbling relaxation rates, with larger CAs typically displaying larger r 1 , as is seen here. However, the few reported high-field r 2 /r 1 ratios are similar (7.0−11), 41,49,50 compared to 9 for MnO pyrr , with 6.7 nm MnO-TETT 46 standing out with an r 2 /r 1 of 3 at 7 T. Similarly sized instances are easier to find at lower fields, where MnO pyrr sits somewhat in the middle range. For example, our r 1 is significantly higher than that for 7 nm MnO-oleate-PEGP 44 (by almost an order of magnitude); however the r 1 for D-glucuronic-acid-coated 2.5 nm MnO NPs is almost 2.5 times higher compared to our system.…”
Section: Relaxometry Of Mno Pyrrcontrasting
confidence: 76%
“…Size is an important factor, as it affects the tumbling relaxation rates, with larger CAs typically displaying larger r 1 , as is seen here. However, the few reported high-field r 2 /r 1 ratios are similar (7.0−11), 41,49,50 compared to 9 for MnO pyrr , with 6.7 nm MnO-TETT 46 standing out with an r 2 /r 1 of 3 at 7 T. Similarly sized instances are easier to find at lower fields, where MnO pyrr sits somewhat in the middle range. For example, our r 1 is significantly higher than that for 7 nm MnO-oleate-PEGP 44 (by almost an order of magnitude); however the r 1 for D-glucuronic-acid-coated 2.5 nm MnO NPs is almost 2.5 times higher compared to our system.…”
Section: Relaxometry Of Mno Pyrrcontrasting
confidence: 76%
“…Afterwards, the diluted RBC suspension (200 μL) was added to PBS (1 mL) as the negative control, to water as the positive control, and to MnCO 3 @BSA nanoparticles at different Mn concentrations (0–100 μM). 28 After incubation at 37°C for 2 h, the released hemoglobin was obtained by centrifugation at 10,000 r/min for 10 min. Absorbance of the obtained supernatant at 570 nm was observed by photometric analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Some methods which do not use fluorescent dye have been introduced. Lai et al found that MnO which has been obtained through the thermal decomposition of an excess of oleic acid (oleic acid: manganese content > 2) displays fluorescence excitation characteristics across its entire visible spectrum 42. To verify its bio-imaging performance, C6 cells were detected following surface modification of TETT, and it was found that cells exhibited blue and green fluorescence at 405 nm and 458 nm, respectively.…”
Section: Mno-based Nanoparticles In Tumor Diagnosis and Therapymentioning
confidence: 99%